Metaphor identification procedure MIPVU: an attempt to apply it to Lithuanian - Urbonaitė, Justina (Taikomoji kalbotyra, 2015)
The aim of this article is to present some insights and reflections as a result of the application of the MIPVU procedure for metaphor identification in Lithuanian and discuss several methodological issues. Firstly, the paper presents the background to the methodology and illustrates its application to Lithuanian. Secondly, the article discusses some difficulties in applying this method to Lithuanian in annotating words as (non)metaphorical. Namely, problematic issues include the following: identification of metaphorical meaning motivated by grammatical cases; demarcation of lexical units, establishing contextual and basic meanings of words based on their definitions provided in available dictionaries of (contemporary) Lithuanian, and the fuzzy boundaries between homonymy and polysemy. As a conclusion, some tentative suggestions are provided regarding more effective application of the MIPVU tool to the analysis of Lithuanian.
Keywords: metaphor; metaphor identification procedure; Pragglejaz; MIPVU